Nghiên cứu ảnh hưởng của vật liệu nano SiO2 điều chế từ tro trấu đến khả năng chống thấm ion clo của bê tông xi măng nhiều tro bay - Thanh Lê, Đặng Thị; Lê Mai, Vương Đặng; Cường, Vũ Việt; Tuấn, Hoàng Anh (Vietnam Journal of Chemistry, 2017)
Silica nanoparticles were successfully extracted from the rice husk ash. The obtained SiO2 powders had monoclinic crystal system, large specific surface area (258.3 m2/g), and particle size (10 to 15 nm). Nano SiO2 prepared from rice husk ash increased the chloride resistance of fly ash cement concrete. The ability to resist chloride penetration increases with the content of using nano-SiO2. When the content of nano-SiO2 is 2 %, the chloride resistance of concrete is optimized (25 % reduction of charge passed compared to concrete not using nano-SiO2). Keywords. Silica nanoparticles, rice husk ash, fly ash cement concretes, chloride resistance of concrete.